Rethinking the justice system in times of emergency and its opportunities - Domínguez Haro, Helder (2020)
The institutional and functional crisis and the declaration of state of emergency have created a new legal framework to reform the old justice system. The new context serves to rethink the justice system and it is the opportunity to change the legal practices and institutions. For example, it was created the «Consejo para laReforma del Sistema de Justicia». This essay reviews the previous proposals to reform the «Consejo». It analyzes the judicial reform of 1958. One conclusion is that, probably, the different reform to the justice system does not benefit anything; but there is a reason to think that the «Consejo para la Reforma del Sistema de Justicia» will be a real change of the judicial system. It is for his legal design. The legal framework of the «Consejo» uses some democratic and constitutional norms. These serve to reassess the trust of citizens and the quality of the justice system.